Synthesis, characterization and surface properties of an organosilicon surfactant - Zhu, Xinhua; Wang, Yanyu; Huang, He; Zhang, Yuqiang; Jia, Xuhong; Zhi, Maoyong (Frontiers in Chemistry, 2026)
In order to explore alternative substances for traditional fluorocarbon surfactants while maintaining high surface activity, this study successfully designed and synthesized an organosilicon surfactant (SiCH) containing a hydroxyl quaternary ammonium salt. Its molecular structure was confirmed by Fourier transform infrared spectroscopy (FT-IR), nuclear magnetic resonance (NMR), and mass spectrometry (MS). This surfactant exhibits excellent thermal stability, with an initial decomposition temperature of 167 °C and minimal residue at high temperatures. The critical micelle concentration (CMC) and the surface tension (γCMC) at the CMC of SiCH are 9.10 mmol/L and 22.81 mN/m, respectively. The organosilicon surfactant–sodium hexanesulfonate (SiCH-SHS) exhibits significant synergistic effect, reducing the CMC and γCMC to 6.88 mmol/L and 21.03 mN/m respectively. The area occupied by a single surfactant molecule at the air/water interface (AS) of the SiCH-SHS is 1.24 nm2, and the pC20 is 2.91. The size distribution of SiCH is unimodal, and they can self-assemble into non-uniform sized spheroidal aggregates (122–295 nm). Moreover, the thermodynamic process of micelle formation of the surfactant was studied through conductivity tests conducted at different temperatures (298.15 − 303.15 K). Thermodynamic analysis indicates that micellization is a spontaneous (ΔGm0 <0), entropy-driven process.